The role of pragmatic competence in teaching Czech as a foreign language and social identity formation - Martina Hrdá; Radim Šíp (Czech Pedagogical Society, 2011)
The authors of this text present the philosophical basis in which the relationshipof communication and integration is seen in a new context. It deals withthe tight involvement of language acquisition in the formation of social identity. Bothare examined in the process of the development of pragmatic competence as the fundamentalcomponent of communicative competence. The alternative stance offered by theauthors underlines and explains the major tendencies of foreign language teaching - todistance themselves from narrowly linguistic approach and to aim at communicationsthoroughly. At the end of the text, the authors introduce a hint of a possible researchdesign that grasps the relationship between pragmatic competence and social identity.